The water extract of Coleus barbatus Benth decreases gastric secretion in rats - Lygia A. Fischman (Memórias do Instituto Oswaldo Cruz., 1991)
Coleus barbatus (Labiatae) Benth is popularly used in Brazil "for the healing of liver and stomach diseases". The water extract (WE 1 to 10 g/Kg, p.o.) of stem and leaves given to rats and mice did not induce signs of intoxication. Preveious treatment of mice with WE (1 g/kg, p.o.) shortened the sleeping time induced by pentobarbital (50 mg/Kg, i.p.) by 37 por cento, althoyugh the extract alone did not increase the spontaneous activity nor did it induce hyperexcitability. In mice WE (2 g/Kg, p.o.) increased the intestinal transit of charcoal by 30 por cento, while reduced gastric secretions ion rats treated with WE (2g/Kg intraduodenal) 3,9 ± 1.0 to 0.5 ± 0.2 ml/4h, respectively). The treatment also reduced the total acid secretion from 34.4 ± 11.0 to 2.7 ± 0.5 mEq/l and raisedgastric pH from 2.2 ± 0.3 to 6.5 ± 0.8. Treatment with WE (2g/Kg, p.o.) protected against gastric ulcers induced by stress (5.3 ± 1.6 and 1.5 ± 0.5 ulcers/cm²), but did nor protect against indonethacin induced ulcers. The results show that the water extract of C barbatus Benth produces mild stimulation of thecentral nervous system and increases intestinal movements. The extract also reduces gastric secretion indicating an antidyspeptic activity, and protects against gastric ulcers induced by stress.